The effects of mentoring programs on primary students’ enjoyment of reading - Aminuyati Aminuyati; Venny Karolina; Carla Queiroz (International Journal of Evaluation and Research in Education (IJERE), 2023)
Mentoring programs in education are known as the involvement of experienced persons to support students’ learning. Concerning improving literacy, mentoring programs aim to help students understand reading materials and improve their reading enjoyment and behaviors. This research aimed to investigate mentoring programs’ impact on primary students’ reading enjoyment. This study, in particular, intended to probe whether the mentoring programs significantly affected students’ reading enjoyment, whether male and female students differed on their reading enjoyment after getting mentoring intervention and whether the periods of mentoring impacted students’ enjoyment of reading. The study used secondary data of the Time to Read Program, a volunteering program conducted in Northern Ireland held by the Business in the Community in cooperation with Education Authority to promote literacy to local primary school students. The sample students in the secondary data used in this study were 250 eight-to-nine years old students. This study used the independent t-test and the ANOVA test to analyze the data. This study failed to find evidence that mentoring programs increased students’ reading enjoyment and that males and females differed in their reading enjoyment after mentoring intervention. However, this study found evidence that mentoring periods significantly improved primary students’ reading enjoyment.